RadalyX: Portable Multimodal Robotic Scanner - Josef Uher; Jana Boháčová; Richard Kadeřábek; Jakub Veselý (e-Journal of Nondestructive Testing)
Robotic Computed Tomography (CT) is proving itself to be a powerful addition to the portfolio of inspection methods [1]. Robots allow for the upscaling of CT measurements on large objects, and the flexibility of robots enables a wide range of scanning trajectories. Our scanner design and geometry calibration processes further make the system fully portable [2]. In other words, the object does not have to “go to the CT machine”; instead, the CT machine “can go to the object.” Advanced inspection of regions of interest is therefore possible. This approach is particularly useful in aerospace and space applications, where the demand for advanced non-destructive inspection is at its highest. The portability of the scanner further expands the range of object sizes that can be inspected. As scanning is less limited by the reach of robotic arms, smaller, more precise robots can be used. In this paper, we will present recent advances in scanning strategies and the results these approaches bring in different situations. Examples not only from aerospace but also from other fields are shown. As a general note, all the 2D/3D X-ray images presented throughout this paper are measured exclusively by the robotic scanner RadalyX.